FEMINISME : ANTARA OTORITER DAN OTORITATIF - Endrizal Endrizal (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
This paper is a philosophical description of women's knowledge. Does gender affect the way and what knowledge will be obtained by someone. If we follow the thesis of historical materialism of Marxism, then the answer is